Det materiella i fokus - Sofi Gerber (Kulturella Perspektiv, 2012)
This article discusses the definition of discourse by Laclau and Mouffe as including also the material, in relation to ethnological applications. It analyses East German material articulations before and after the Fall of the Wall through biographic interviews with people grown up in the GDR. By using the concept of dislocation, the author shows how material things, such as the Berlin Wall, buildings and everyday objects are objectified in a certain historical setting, but politicalized in another. In the dislocation between the social and the political, the material is part of antagonistic articulations as well as of new hegemonic interventions. Thereby, the material objects not only change meanings, but also contribute to which new identifications that are available, possible and attractive.